Illustration of the emerging capabilities of SARAL/AltiKa in the coastal zone using a multi-platform approach. Issue 1 (1st January 2015) - Troupin, Charles; Pascual, Ananda; Valladeau, Guillaume; Pujol, Isabelle; Lana, Arancha; Heslop, Emma; Ruiz, Simón; Torner, Marc; Picot, Nicolas; Tintoré, Joaquín
Highlights Glider data were acquired along a SARAL/AltiKa track in August 2013 in the Ibiza Channel. Satellite altimetry, HF radar and glider data are interpolated and filtered to compute the cross-track velocity. All the platforms showed the existence of a 25–30 km width coastal jet with velocities larger than 20 cm/s. Filtered 40 Hz data provided geostrophic current about 10 km from the coast.